Methionine Sulfoxide Reductase A (MsrA) and Its Function in Ubiquitin-Like Protein Modification in Archaea - Xian Fu (American Society for Microbiology, 2017)
ABSTRACT Methionine sulfoxide reductase A (MsrA) is an antioxidant enzyme found in all domains of life that catalyzes the reduction of methionine-S-sulfoxide (MSO) to methionine in proteins and free amino acids. We demonstrate that archaeal MsrA has a ubiquitin-like (Ubl) protein modification activity that is distinct from its stereospecific reduction of MSO residues. MsrA catalyzes this Ubl modification activity, with the Ubl-activating E1 UbaA, in the presence of the mild oxidant dimethyl sulfoxide (DMSO) and in the absence of reductant. In contrast, the MSO reductase activity of MsrA is inhibited by DMSO and requires reductant. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis reveals that MsrA-dependent Ubl conjugates are associated with DNA replication, protein remodeling, and oxidative stress and include the Ubl-modified MsrA, Orc3 (Orc1/Cdc6), and Cdc48d (Cdc48/p97 AAA+ ATPase). Overall, we found archaeal MsrA to have opposing MSO reductase and Ubl modifying activities that are associated with oxidative stress responses and controlled by exposure to mild oxidant. IMPORTANCE Proteins that are damaged by oxidative stress are often targeted for proteolysis by the ubiquitin-proteasome system (UPS). The mechanisms that control this response are poorly understood, especially under conditions of mild oxidative stress when protein damage is modest. Here, we discovered a novel function of archaeal MsrA in guiding the Ubl modification of target proteins in the presence of mild oxidant. This newly reported activity of MsrA is distinct from its stereospecific reduction of methionine-S-sulfoxide to methionine residues. Our results are significant steps forward, first, in elucidating a protein factor that guides Ubl modification in archaea, and second, in providing an insight into oxidative stress responses that can trigger Ubl modification in a cell.